Therapeutic benefits of melatonin beyond sleep regulation: a comprehensive review - Santosh Krishnappa Munirajureddy; Usha Humbi; Akash Nalajala; Bhavishya Nerella; Vishnu Arumainathan (International Journal of Basic & Clinical Pharmacology, 2026)
Melatonin is an endogenous indoleamine primarily synthesized by the pineal gland and is best known for its role in regulating the sleep–wake cycle and circadian rhythm. However, accumulating evidence suggests that melatonin exerts a wide range of biological actions beyond sleep regulation. It displays antioxidant, anti-inflammatory, and immunomodulatory properties, and has been investigated for potential benefits in neurological, cardiovascular, metabolic, respiratory, gastrointestinal, hepatic, renal, reproductive, oncological, and aging-related disorders. In addition, melatonin may influence gene regulation, mitochondrial function, appetite control, energy homeostasis, and thermoregulation, highlighting its pleiotropic therapeutic profile. Preclinical and clinical studies have also explored novel formulations, including sustained-release systems and nanotechnology-based delivery approaches, to improve its bioavailability and therapeutic utility. Although melatonin is generally considered safe and well tolerated, clinical evidence remains heterogeneous, and variations in dose, formulation, and treatment duration continue to limit standardization. Therefore, larger randomized controlled trials are needed to clarify its efficacy, optimize dosing strategies, and define its long-term safety across different disease settings. Overall, melatonin represents a promising multifaceted therapeutic agent with expanding clinical relevance beyond its traditional use in sleep medicine.